Management of Prolapsed Uterus-Grade I with Siddha External Therapy Aloe Vera and Tripala Bandage: A Case Study - S, Esaivani; R, Susila; T, Kavitha; A, Usha; P, Sathiyarajeswaran (Archives of Clinical and Medical Case Reports, 2020)
Pelvic organ prolapse is a common problem among aging women. About 50% of parous women have Pelvic organ prolapse. Hysterectomy is one of the most preferred treatments for prolapsed Uterus. The Risk of post hysterectomy prolapse is 5.5 times higher if hysterectomy was performed because of prolapsed uterus. There is a need for proper management of prolapsed uterus without any complications. Siddha, a traditional system of medicine found to provide better management for Prolapsed Uterus. A 36 year old female patient with the complaints of constipation, stress urinary incontinence, urgency of urine, feeling mass in vagina while washing genitalia, uncomfortable while sitting since 1 year was reported to Siddha Reproductive and child health Outpatient Department. It was diagnosed as Prolapsed Uterus Grade I based on symptoms, Physical examination and Ultra sonogram Pelvis. She was treated with Aloe Vera and Tripala Bandage, a Siddha external therapy along with internal medicines. Pelvic floor disability Index score was used to assess the symptoms severity before and after the treatment. After treatment with External therapy and Internal medicines for one month clinical symptoms were subsided and patient feels good and the Quality of life improved. This case report highlights that Prolapsed uterus Grade I can be managed with Aloe Vera and Tripala bandage effectively and it was cost effective.